HUBUNGAN PERILAKU CUCI TANGAN PAKAI SABUN DENGAN KEJADIAN DIARE PADA ANAK USIA SEKOLAH DI SEKOLAH DASAR NEGERI MANGKANGKULON 03 SEMARANG - Windyastuti -; Nana Rohana; Rudi Alex Santo (Universitas Muhammadiyah Semarang, 2017)
Background: Diarrhea is the incidence of bowel movements with amore liquid consistency than its base, with a frequency of 3times or more for 1day. Diarrhea is an infectious disease can be transmitted throughun clean hands. A person who holds a food with a low personal hygiene and sanitation practices are not good, often contaminate food by microorganism. The prevalence of diarrhea is still high school kids as many as149.404 people with children in 2010 were caused by, among others, they are in the habit of hand washing procedures are not appropriate. The purpose of this study was to determine the relationship of handwashing with soap behaviour with diarrhea incidence in children of school age in primary school Mangkangkulon Semarang.Methods: This study used across-sectional approach. The research use disdescriptive correlational. The data was collected using a questionnaire instrument. This study uses the total samples many as74 people. Data were analyzed bychi-square test and Fisher's exact test alternatives.Results: The results showed that the highest number of respondents according to the behavior of handwashing with soap is handwashing behavior of respondents with good criteria as many as 57people(77.0%) and the highest number of respondents according to the incidence of diarrhea is respondents with categories no diarrhea as many as59 people(79.7%). Results obtained p value=0.000(p value <0.05) which means that Ho is rejected and Ha is accepted, then there isa relationship of handwashing with soap behaviour with diarrhea incidence in children of school age in primary school Mangkangkulon Semarang.Conclusion:There isa relationship of handwashing with soap behaviour with diarrhea incidence in children of school age in primary school Mangkangkulon Semarang.Keywords:behavior, handwashing with soap, diarrhea